Akibat Hukum Bagi Pekerja yang Tidak Melaksanakan Employee Branding: Analisis Yuridis Terhadap Kewajiban dan Upaya Hukum - Togatorop, Pricelia Anggita; Ambarwati, Mega Dewi (Media Hukum Indonesia (MHI), 2025)
Employee branding is a corporate approach to create a positive image through employee behavior and performance. This study examines the legal implications for employees who fail to apply employee branding, the legal frameworks that regulate it, and the legal actions that can be pursued. The research employs a normative juridical method with an analysis of laws and case studies. Findings indicate that violations of employee branding may lead to penalties ranging from warnings to dismissal. The legal grounds cover Labor Law, company policies, and employment contracts. Available legal actions include mediation, arbitration, and lawsuits in the Industrial Relations Court